Total deposition of inorganic nitrogen to Norway spruce forests – Applying a surrogate surface method across a deposition gradient in Sweden. (15th November 2019) - Karlsson, P.E.; Pihl Karlsson, G.; Hellsten, S.; Akselsson, C.; Ferm, M.; Hultberg, H.
Abstract: The dry and wet deposition of nitrate, NO3 −, and ammonium, NH4 +, were estimated for Norway spruce forests at ten monitoring sites across Sweden for the years 2014–2017. The particulate dry deposition was estimated based on measurements using Teflon string samplers as surrogate surfaces, in combination with the net throughfall deposition for sodium (throughfall subtracted with wet deposition). The wet deposition was estimated from bulk deposition measurements, corrected for dry deposition to the collectors. There was a strong gradient for total inorganic nitrogen (N) deposition across Sweden from north to southwest, ranging from 2 to 20 kg N ha −1 yr −1 . The values for N deposition derived from measurements were for most sites exceeding the corresponding values derived from modelling with the MATCH and EMEP models, in southern Sweden by up to 4–6 kg N ha −1 y −1 . Based on comparisons between total and throughfall deposition, the canopy uptake of atmospheric N deposition to Norway spruce forests in Sweden was estimated to be in the range of 0–7 kg N ha −1 yr −1 . Graphical abstract: Image 1 Highlights: Dry deposition of particulate N to forests was estimated with surrogate surfaces. The total deposition of N was higher compared with model predictions. The canopy uptake of N to spruce in Sweden was on the order of 0–7 kg N ha −1 yr −1 . The critical load for N deposition to spruce forests was exceeded at most sites.